Magična moć opscenih reči u ženskoj reveni - Stevanović, Lada (Wydawnictwo Naukowe UAM, 2012)
The theme of this paper is the magic power of the obscene words and jokes in traditional Serbian culture, on the example of women’s only festival revena in Banat. This ritual represents one day holiday that was celebrated in the beginning of spring, before the Eastern Fast. During revena women gathered for a celebration during which their behavior was completely different than usual, transgressing all the strict norms that prevailed in everyday reality of patriarchal society. Except for the excessive drinking and eating, women expressed their sexuality freely and they spoke about it in the most obscene way. Apart from the verbal part, the ritual of revena had also its performative side. Thus women were proving their female sex by raising the skirt (in the Kumane village), and this act functioned as some kind of pass to enter the revena. During the holiday, some women were dressed up as men in order to fulfill the necessary male roles for the sexual games, because no man (except for the musician) was allowed to be present on this holiday. The analysis in this paper, devoted above all to the magic power of the obscene language in the traditional culture, is inscribed into the Bakhtin’s theory of carnival. It is applied here not only to the carnivalesque behavior, but also to the concrete verbal obscene content. These obscenities are inseparable from laughter, so the magic power of laughter (as defined by Veselin Čajkanović) is also analyzed in this paper, and, apart from appearing in revena, it represented important part of the funeral ritual.
Magic Power of the Obscene Language in Womens’ Revena
Keywords: Obscene language; Revena; Magical laughter; Life; Death; Bakhtin